The effects of earnings management on information asymmetry and stock price synchronicity - Dong Quang Dang; Ioannis Korkos; Weiou Wu (Cogent Economics & Finance, 2023)
In this study, we test whether earnings management has a positive impact on information asymmetry as well as whether earnings management has a negative impact on stock return synchronicity to investigate how discretionary accrual earnings management affects the imbalance of information and the co-movement of stock prices in Vietnam. We utilise the Pooled OLS (OLS), Random Effects (RE), Fixed Effects (FE), and System GMM models to evaluate our dataset collected from 356 non-financial companies listed on the Hochiminh City Stock Exchange (HOSE) spanning from 2012 to 2021. We find that in Vietnamese market earnings manipulations through accrual based falsify the market and cause information asymmetry leading to adverse effects on market liquidity and stock price synchronicity. Additionally, our findings exhibit greater co-movements between stock prices and earnings management at the larger firms with long incorporation history and are audited by Big Four Audit firms due to their credibility. These findings are particularly useful for foreign investors in making investment decisions as we found that their influences on earnings management in Vietnamese market is limited.
Keywords: G14; G31; G32; 330; audit quality; earnings management; information asymmetry; quality of information; stock price synchronicity